Dissecting the ATP hydrolysis pathway of bacterial enhancer-binding proteins. (22nd January 2008) - Bose, Daniel; Joly, Nicolas; Pape, Tillmann; Rappas, Mathieu; Schumacher, Jorg; Buck, Martin; Zhang, Xiaodong
Abstract : bEBPs (bacterial enhancer-binding proteins) are AAA+ (ATPase associated with various cellular activities) transcription activators that activate gene transcription through a specific bacterial σ factor, σ 54 . σ 54 –RNAP (RNA polymerase) binds to promoter DNA sites and forms a stable closed complex, unable to proceed to transcription. The closed complex must be remodelled using energy from ATP hydrolysis provided by bEBPs to melt DNA and initiate transcription. Recently, large amounts of structural and biochemical data have produced insights into how ATP hydrolysis within the active site of bEBPs is coupled to the re-modelling of the closed complex. In the present article, we review some of the key nucleotides, mutations and techniques used and how they have contributed towards our understanding of the function of bEBPs.